CONTRIBUTION OF KERINCI TRADITIONAL INSTITUTIONS IN RESOLUTION OF SYIQAQ DISPUTES - Elmina, Sovia; Sulfinadia, Hamda; Ahmad Nadzri, Amirulhakim Bin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Kumun Debai has a traditional institution as a judiciary in resolving customary disputes including syiqaq disputes. The Kumun Debai traditional institution has had many successes in resolving disputes peacefully. However, people today who are in the midst of domestic conflicts, such as syiqaq , prefer to take legal action in the hope that a divorce will be granted. The aim of this research is to examine the process of resolving syiqaq disputes through Traditional Institutions in Kumun Debai. This research is qualitative in nature, in this research the data collection technique used is an interview technique which is considered primary data. The results of the research show that the process of resolving syiqaq disputes through traditional institutions is that first, traditional institutions receive complaints from disputing parties to help resolve the dispute, secondly, traditional institutions attend invitations from disputing parties at the specified time, thirdly , traditional institutions request each parties explain the problems that occur, fourth of the problems raised by traditional institutions research, study, draw conclusions and provide direction or advice to the parties in dispute in accordance with customary law, fifth traditional institutions ask for decisions from both parties to the dispute, sixth settlement by apologizing and the parties make an agreement either verbally or in writing.